Globalne rankingi uniwersytetów i akademicka gra o status - Gromkowska-Melosik, Agnieszka (Wydawnictwo Naukowe UAM, 2015)
Neoliberal struggle for social status and high financial rewards is also present in the field of education. My article is devoted to the problems of university rankings, which is also part of contemporary neoliberalism. I am convinced that rankings create to some extent contemporary academic reality. One can say that rankings dilute the traditional mission (and vision) of the university. Universities are treated as big companies, driven by success and profits. In the article the rankings issues are presented including the criticisms of their consequences.
Global University Rankings and the Academic Status Game
Keywords: rankings; univeristy; neoliberalism